Towards Ruthenium-Based Building Blocks for CuAAC Click Reactions: Challenges in Generating Ruthenium(II) Polypyridine Alkynes - Zabarska, Natalia; Sorsche, Dieter; Heinemann, Frank Wilhelm; Glump, Susanne; Rau, Sven (European Journal of Inorganic Chemistry, 2015)
Ag+-free complexation of alkyne-bipyridines at ruthenium(II) polypyridine centers proceeds with surprisingly low yields. The alkyne-bipyridine-substituted ruthenium(II) polypyridine complexes in this work were characterized by NMR spectroscopy, ESI spectrometry, and single-crystal X-ray structural analysis. A detailed analysis of the side products revealed an unexpected carbon-carbon alkyne bond splitting promoted by the ruthenium(II) center, leading to the formation of a CO-Ru-II species, methyl-bipyridine, and a methyl-bipyridine-substituted ruthenium(II) complex accompanying the target product. The side products were characterized using complimentary methods including X-ray crystallography. A possible mechanism is suggested based on these side products and exemplary reaction studies.
Keywords: Alkyne ligands; Carbonyl ligands; Click chemistry; Coordination modes; Ruthenium